Herramienta digital para el registro de cirugías con dispositivos médicos implantables y la visualización de datos. - Valdeperas-Soto, María José (Instituto Tecnológico de Costa Rica, 2018)
Have you ever wondered, how the documentation of surgeries with implants is managed or, even more importantly, how to access the information of those documents? When dealing with the medical industry, we may think that all methods implemented are always secure and digital, however, the reality in Costa Rica is different. Even though medical companies try to keep track of records and access their content "easily", the documentation continues to be done manually and is stored in logs. These methods may generate loss documents, implicate a high demand of time when searching a specific record and when trying to obtain statistic data such as implant placement, clients and number of surgeries performed, the search has to be done manually in Excel. The following project presents the stages of development, from the collection of information and usability tests, to the development of the application interface proposal. Its objective is to propose a digital tool for the registration of surgeries with implants that will facilitate the access to the information of the registers, both at the level of search and data visualization.
Proyecto de Graduación (Bachillerato en Ingeniería en Diseño Industrial) Instituto Tecnológico de Costa Rica, Escuela de Diseño Industrial, 2018
Keywords: Implantes; Cirugías; Documentación; Visualización de datos; Tecnología digital; Research Subject Categories::MEDICINE::Surgery::Surgical research